2019
DOI: 10.1186/s12870-019-2018-1
|View full text |Cite
|
Sign up to set email alerts
|

SWATH-MS-facilitated proteomic profiling of fruit skin between Fuji apple and a red skin bud sport mutant

Abstract: BackgroundApple is one of the most popular fruit crops world-wide and its skin color is an important quality consideration essential for commercial value. However, the strategy on genetic breeding for red skin apple and the genetic basis of skin color differentiation is very limited and still largely unknown.ResultsHere, we reported a bud sport mutant of Fuji apple with red skin color and enhanced anthocyanins accumulation. Quantitative SWATH-MS (sequential window acquisition of all theoretical spectra-mass sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…ABA was also involved in the regulation of self-protection processes (Ahmadi, Agharezaee, Kamgar-Haghighi, & Sepaskhah, 2014). Omics research is widely used to find the underlying molecular mechanism behind observed physiological changes (Chen et al, 2019;Zhu et al, 2017Zhu et al, , 2018. Root proteomic analysis showed that proteins involved in ABA signaling, amino acid synthesis, and N remobilization were up-regulated in the soil drying phase of AWD irrigation, when compared with CF irrigation (Li, Nong, et al, 2016;Li, Azeem, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…ABA was also involved in the regulation of self-protection processes (Ahmadi, Agharezaee, Kamgar-Haghighi, & Sepaskhah, 2014). Omics research is widely used to find the underlying molecular mechanism behind observed physiological changes (Chen et al, 2019;Zhu et al, 2017Zhu et al, , 2018. Root proteomic analysis showed that proteins involved in ABA signaling, amino acid synthesis, and N remobilization were up-regulated in the soil drying phase of AWD irrigation, when compared with CF irrigation (Li, Nong, et al, 2016;Li, Azeem, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The different colors of apple fruits were mainly caused by the difference of anthocyanin accumulation. Abundant apple germplasm resources and color mutants provide excellent materials for the study of plant anthocyanin metabolism [ 28 ]. In addition, the shape of the branches usually affects the yield and quality of the fruit.…”
Section: Discussionmentioning
confidence: 99%
“…The present results also provide a fast and efficient means of alleviating the damage caused by HT stress during the meiosis stage of young spikes of rice, which may contribute to the regulation of rice cultivation. Furthermore, corporation of innovative multi-omics technology may help us unravel the molecular dynamics of this interesting research topic 45,46 .…”
Section: Discussionmentioning
confidence: 99%